0297 Occupational exposure to organic dust and risk of developing rheumatoid arthritis. (21st August 2017) - Ilar, Anna; Gustavsson, Per; Wiebert, Pernilla; Bengtsson, Camilla; Klareskog, Lars; Alfredsson, Lars
Abstract : Objective: Airborne exposure to inorganic dust is a contributor to rheumatoid arthritis (RA). We therefore wanted to investigate potential risks from exposure to organic dust. Methods: This population-based case-control study consisted of individuals living in Sweden during 1968–2012. RA patients were enrolled from the Swedish Rheumatology Quality Register. To each case we matched ten controls from the population register on sex, parish and age. We collected the participants' job titles from national population and housing censuses carried out 1960, 1970, 1975, 1980 and 1990. Job-exposure matrices were applied to the job titles to estimate ever exposure to oil mist/cutting fluids, wood-, animal-, paper-, textile-, flour- and other organic dust from 1955–1995. We used conditional logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for ever exposure vs. never exposure in relation to seropositive or seronegative RA. Results: In total, 237 243 women and 98 136 men were included in the analysis. Men exposed to animal dust (OR: 1.3, 95% CI: 1.2–1.5), oil mist/cutting fluids (OR: 1.1, 95% CI: 1.1–1.2) and other organic dusts (OR: 1.3, 95% CI: 1.2–1.4) had an increased risk of seropositive RA, whereas wood dust (OR: 1.2, 95% CI: 1.1–1.4), animal dust (OR: 1.3, 95% CI: 1.1–1.6) and other organic dusts (OR: 1.2, 95% CI: 1.1–1.4) increased the risk of seronegative RA. Women had no significantly increased risk of RA from organic dust exposure. Conclusions: Certain organic dusts are associated with increased risks of RA in men.